Optimisation of kombucha fermentation : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Auckland, New Zealand - Gangurde, Ashwini Navin (Massey University, 2022)
Kombucha is a slightly acidic, self-carbonated and refreshing fermented beverage made from sugared tea by the symbiosis of yeast and acetic acid bacteria (AAB). The symbiotic culture exists in a biofilm commonly called ‘symbiotic culture of bacteria and yeast’ (SCOBY) and fermented broth. Kombucha is popular in many regions of the world and its production relies on natural fermentation by an undefined complex mixed starter culture. Therefore, the fermentation process results in products of variable quality among the producers and even by the same individual processor. The efficiency of non-alcoholic Kombucha fermentation is determined by the final ethanol content, residual sugar and acidity at the end of fermentation. Kombucha beverages sold in the market are biologically active, therefore the fermentation continues during storage as the yeast and bacteria thrive on the residual sugar present in the final product. During storage, secondary fermentation generates the desired carbonation and also reduces residual sugar in the final products, but the microbial activity may also result in the production of beverages with higher alcohol levels than permissible. In New Zealand, Kombucha is categorised as a non-alcoholic beverage with alcohol of no more than 1.15% ABV or 0.5 % ABV (Australia). Kombucha brewers generally find it difficult to produce consistently high-quality products with low alcohol as stipulated by the Food Standards Australia New Zealand regulations. The present study aimed to optimise the fermentation process using robust experimental plans to produce a stable low alcohol fermented Kombucha with low sugar. The present research work was conducted in three Phases and the experiments were repeated twice with duplicate analyses. Phase 1 involved selection of the best fermentation conditions to propagate the Kombucha starter culture comprising ‘fermented broth and cellulose pellicle (SCOBY)’ using fermented broth as the starting material. The factors used in this Phase were sugar (3% and 4.7%, w/v) and tea (0.3% and 0.5%, v/v), inocula (12.5% and 20%, v/v), fermentation temperature (22℃ and 24℃) and the formulations were fermented for 14 days. To select the best propagation conditions for the growth of starter culture comprising SCOBY and fermented broth, acidity, total soluble solids (TSS), weight of SCOBY and microbial concentrations (yeast, AAB, total counts) were determined during fermentation. Yeast were enumerated using yeast extract glucose chloramphenicol agar (YGC) agar, AAB were enumerated by yeast extract peptone mannitol (YPM), and total counts by plate count agar (PCA). The best fermentation conditions for the growth of the culture were then selected and adopted for use in the subsequent experiments. Phase 2 investigated the best conditions for the fermentation of Kombucha using a combination of SCOBY and fermented broth as starter culture, in two stages (Stage 1 and Stage 2). Two sugar concentrations (3% and 4.7%, w/v) and two fermentation temperatures (22℃ and 24℃) were used in Stage 1 to determine the optimum sugar concentration and fermentation temperature required to ferment Kombucha for 9 days (primary fermentation). Stage 2 investigated the effect of filtration on Kombucha during storage (4°C) for a week, post-primary fermentation (9 days). Physico-chemical (TSS, acidity, colour) and microbiological (yeast, AAB, total counts) characteristics of the beverages were determined in the two stages including the measurement of colour (CM-5 Konica Minolta spectrophotometer Japan). The beverages were also evaluated by 5-7 focus sensory panellists in Stage 1 and consumer sensory panellists (n=35) in Stage 2, using a 9-point hedonic scale. The storage stability (4 °C) of the selected formulations from Stage 2 (Phase 2) were evaluated in Phase 3 for three weeks (4℃). In addition to the analyses conducted in Phase 2, concentrations of sugars, ethanol organic acids and antioxidants were determined during fermentation and storage. The developed beverages were also evaluated by consumer sensory panellists (n= 108). Results showed that the formulation (Phase 1) that contained 3% sugar, 0.5% tea, 20% fermented broth and fermented at 24℃ produced the best growth of the starter culture. In Stage 1 (Phase 2), titratable acidity (T.A.) and microbial counts increased (p<0.05), while pH, TSS (p<0.05) and overall acceptability by a focus sensory panel decreased for samples fermented with low sugar concentration (3%, w/v) at 22℃ and 24℃. In Stage 2, T.A. and microbial counts increased (p<0.05), while pH, TSS and consumer sensory scores decreased (p<0.05) for the Kombucha samples (filtered and unfiltered) fermented at 24 ℃. Samples (filtered and unfiltered) containing 4.7% sugar and fermented at 22 °C received higher overall consumer sensory scores (7.30±0.32 ;6.98 ±0.19) compared to the sample that contained 4.7% sugar and fermented at 24℃. Therefore, this formulation (4.7% sugar; fermentation temperature 22℃) was selected for further evaluation of the filtered and unfiltered samples in Phase 3. In Phase 3, the filtered beverage containing 4.7% sugar, 0.5% tea, 20% fermented broth and fermented at 22℃ received the highest sensory scores for overall acceptability (7.26±0.88) after storage for three weeks (4°C). The lower acidity, ethanol, and sugar (sweetness) of filtered samples (p<0.05) compared to unfiltered samples may have contributed to the better overall liking by the panellists. The lower levels of organic compounds in the filtered sample may be due to reduced metabolic activities caused by the partial removal of trapped cultures in the matrices of the cellulose during filtration. The colour of the fermented beverages was stable during fermentation and no significant changes were observed during storage for 3 weeks (p<0.05). Overall, the filtered sample contained higher concentrations of antioxidants than the unfiltered which may be beneficial to human health. In conclusion, low alcohol Kombucha was successfully produced after filtration, post-primary fermentation at low temperature. The ethanol content of the filtered beverage was <0.5% ABV, which complied with the Australia NZ Food Standards Authority regulation. Furthermore, the residual sugar in the filtered beverage was markedly lower than reported in previous studies. The optimised beverage was stable during refrigerated storage and was well accepted by sensory panellists. The beverages had a pH<4.6, which is generally considered as safe. Therefore, the optimised Kombucha fermentation process resulting from this study has potential for commercialisation. However, further work is required to integrate the filtration step and scale-up.
The following were removed for copyright purposes: Figure 2.8 (= Bai et al., 2008 Fig 3) & Figure 2.10 (= Lin et al., 2013, Fig 2).
Keywords: 400405 Food engineering